FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERINVESTASI SAHAM DI PASAR MODAL SYARIAH BAGI GENERASI MILENIAL DI MADURA - Muhtadi, Ridan; Fitriyani, Novita Ayu; Herachwati, Nuri (Ulumuna: Jurnal Studi Keilsman, 2022)
The purpose of this study is to examine or analyze the Factors Influencing Interest in Investing in Islamic Capital Markets for Millennials in Madura. The variables used are Risk, Income and Knowledge level. The Millennial Generation living in Madura who are interested in investing in Islamic Capital Markets is the population of this study. While the sample was chosen using the purposive sampling technique. In selecting this sample, there were 100 respondents from all 4 districts in Madura. The main information used in this investigation came from structured interviews with the help of a questionnaire. Multiple regression analysis is the data analysis used in this study. Whereas the Knowledge Variable is the result of the conclusion that it has a positive and significant effect on Interest in Investing in Shares in the Islamic Capital Market for Millennial Generation in Madura while the Risk and Income Level Variables have a positive but not significant effect on Interest in Investing in Shares in the Islamic Capital Market for Millennial Generation in Madura. Keywords: Islamic Capital Market; Share; Millennial Generation; Interest; Investation